Novel microguidewire-assist (MGA) manoeuver for coil embolisation of an unruptured middle cerebral artery aneurysm. (27th August 2018) - Maeda, Kazushi; Otsuji, Ryosuke; Uno, Junji; Gi, Hidefuku
Abstract : We describe here a novel yet very simple technique, called microguidewire-assist (MGA) manoeuvre, for coil embolisation of unruptured intracranial aneurysms. A 79-year-old woman with a small, broad-necked middle cerebral artery (MCA) bifurcation aneurysm that incorporated the orifice of the acute-angled M2 superior trunk underwent coil embolisation. Since the balloon assist technique was not feasible, we inserted and retained only the microguidewire through M1 to the M2 superior trunk; subsequently, with appropriate use of the microguidewire, coil embolisation was completed. The MGA manoeuvre resulted in slight vessel straightening and subsequent changes in the angulation of the aneurysmal neck, with which stable placement of the platinum coil was successfully accomplished. For coil embolisation of small, broad-necked MCA aneurysms that partially straddle the M2 trunk, this manoeuvre might provide an effective therapeutic alternative if other techniques are not feasible.